2018
DOI: 10.1159/000488892
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment and Dementia Show Contrasting Associations with Risk of Cancer

Abstract: Background: To investigate and to compare the relation between dementia and cancer with the association between mild cognitive impairment (MCI) and cancer. Methods: A total of 13,207 persons from the Rotterdam Study were followed between 1990 and 2013 for the onset of dementia and cancer (sample 1). Between 2002 and 2005, a subset of 5,181 persons underwent extensive cognitive testing for MCI and subsequently were followed up for cancer until 2013 (sample 2). We used Cox proportional hazard models to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In a first attempt to do so, we investigated the risk of cancer in persons with MCI and compared this with the risk of cancer in dementia patients in a population-based prospective cohort study. 20 In this study, we showed that persons with MCI tended to have an increased risk of developing cancer VAN DER WILLIK ET AL. | 9 of 12 (HR 1.24, 95% CI 0.99-1.58), which is in contrast with the decreased cancer risk among patients with dementia (HR 0.59, 95% CI 0.41-0.68).…”
Section: Preclinical Stagesmentioning
confidence: 66%
See 2 more Smart Citations
“…In a first attempt to do so, we investigated the risk of cancer in persons with MCI and compared this with the risk of cancer in dementia patients in a population-based prospective cohort study. 20 In this study, we showed that persons with MCI tended to have an increased risk of developing cancer VAN DER WILLIK ET AL. | 9 of 12 (HR 1.24, 95% CI 0.99-1.58), which is in contrast with the decreased cancer risk among patients with dementia (HR 0.59, 95% CI 0.41-0.68).…”
Section: Preclinical Stagesmentioning
confidence: 66%
“…Interestingly, multiple studies suggest an inverse association between cancer and dementia, in particular for Alzheimer disease (AD). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In 1990, Yamada et al investigated risk factors for dementia in atomic-bomb survivors and observed that the odds of having cancer prior to AD was 70% lower in patients with AD compared to persons without AD. More than a decade later, longitudinal studies confirmed that cancer patients were at a decreased risk of developing dementia.…”
Section: Dementia Patients and The Risk Of Dementia In Patients With mentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to etiology, research has been done on diet [33][34][35][36] or lifestyle such as smoking [37,38] as a risk factor, and laboratory assessments, for example, inflammatory markers in association with cancer [31,[39][40][41]. Furthermore, the association between cognition and cancer was studied [42,43]. We have confirmed the positive association between a high baseline total cholesterol level and colorectal cancer (CRC) during follow-up, an association which was modified by dietary polyunsaturated fatty acids [35].…”
Section: Main Findings In the Last 3 Yearsmentioning
confidence: 99%
“…Cancer and neurodegenerative disease, including AD as its most common form, may be seen as two opposite ends in cell proliferation. Yet they share biological and clinical characteristics, including dysregulations in key DNA repair and inflammation processes, an increasing incidence with advancing age, and rapid disease progression after diagnosis [6,7]. Moreover, they share a complex inheritance pattern with genetic pleiotropy [8].…”
Section: Introductionmentioning
confidence: 99%